Perioperative posterior ischemic optic neuropathy (PION) after open aortic surgery - Jonathan Lovis; Juan Antonio Celi de la Torre; Robert Seelos; Nicholas Attigah; Misha Pless; Maani Hakimi (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
Perioperative posterior ischemic optic neuropathy (PION) is a rare but potentially devastating condition. A correlation of PION with major surgical procedures has been established, particularly in cases of spine and cardiovascular surgery. The present case report describes a 72-year-old, male patient who developed PION after open aortic surgery, subsequently partially recovering from his visual deficit, which is an atypical feature for PION. Preventive measures as well as improvement of this condition's management depend on understanding its risk factors.